A framework for organizational change to promote inclusion of people with disabilities in museums and science centers - Vicente, Ana Carolina Alves; Norberto Rocha, Jessica (Frontiers in Education, 2025)
Initiatives to include people with disabilities (PWD) in museums and science centers have been documented worldwide for over 80 years; however, there is still a need to implement systematic changes to sustain inclusive practices over time. Including people with disabilities in museums and science centers requires intentional efforts from these organizations. While research from various fields has explored museums' accessibility and inclusion strategies for PWD, few studies examine them from an organizational change perspective. We propose a framework outlining aspects that favor organizational change in museums and science centers, along with areas and actionable recommendations. This framework can support the complex process of organizational change to promote inclusion and accessibility for PWD and aid future research and practice.